2018
DOI: 10.1038/s41598-018-28909-6
|View full text |Cite
|
Sign up to set email alerts
|

Transient localized surface plasmon induced by femtosecond interband excitation in gold nanoparticles

Abstract: Localized surface plasmon resonance (LSPR) is essentially a collective oscillation of free electrons in nanostructured metals. Interband excitation may also produce conduction-band electrons above the Fermi level. However, a question here is whether these excited electrons can take part in plasmonic oscillation. To answer this question, femtosecond pump-probe measurements on gold nanoparticles were performed using interband excitation, where the pump pulse produced a large amount of electrons in the sp-conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 19 publications
6
52
0
Order By: Relevance
“…37,61 Additionally, it has been reported that excitation at (or close to) the plasmon resonance (here 532 nm) is less efficient due to delocalized field distribution 65,66 or ultrafast plasmon band bleaching. 67 Indicative of the latter is also the observation the bubble formation threshold in the current experiment is found at about 56 J m À2 , which is not much lower than the previously recorded threshold of 80 J m À2 at 400 nm (femtosecond pulses) 61 or 50 J m À2 at 355 nm (picosecond pulses) 68 for similarly sized gold particles, despite the absorption cross section being enhanced by a factor of 2 at 532 nm. Altogether, we can secure the general caloric scale for the excitation of the gold nanoparticle suspension, noting that melting is observed above 120 J m À2 .…”
Section: Caloric Prediction Of Phase Behavioursupporting
confidence: 57%
“…37,61 Additionally, it has been reported that excitation at (or close to) the plasmon resonance (here 532 nm) is less efficient due to delocalized field distribution 65,66 or ultrafast plasmon band bleaching. 67 Indicative of the latter is also the observation the bubble formation threshold in the current experiment is found at about 56 J m À2 , which is not much lower than the previously recorded threshold of 80 J m À2 at 400 nm (femtosecond pulses) 61 or 50 J m À2 at 355 nm (picosecond pulses) 68 for similarly sized gold particles, despite the absorption cross section being enhanced by a factor of 2 at 532 nm. Altogether, we can secure the general caloric scale for the excitation of the gold nanoparticle suspension, noting that melting is observed above 120 J m À2 .…”
Section: Caloric Prediction Of Phase Behavioursupporting
confidence: 57%
“…This blue‐shift is assigned to the cooling of hot electron population of AuNI via both elastic and inelastic electron scattering processes that typically occur in sub‐picosecond timescales. [ 41–43 ] Now, as the individual spectral positions of both the bright excitons (X 0 A and X 0 B ) are already known in WS 2 , the Rabi‐splitting energy can be calculated by directly solving E + and E − . The extracted individual Rabi‐splitting energies (Ω R ) are found to be 269 ± 26 and 246 ± 7 meV for X 0 A ‐P and X 0 B ‐P, respectively, in the time domain, by fitting the transient peak positions of E + and E − with Equation ().…”
Section: Resultsmentioning
confidence: 99%
“…as well as the constituent material, the size and shape of the NPs, can all play a crucial role in the e-gas heating and in the energy-relaxation pathway. [23][24][25][26][27][28][29][30][31][32] Additionally, the temperature dependence of the material paratemers (e.g., electronic specific heat, [33][34][35] interface thermal conductivities, [36] etc.) will all affect the actual relaxation dynamics.…”
Section: Introductionmentioning
confidence: 99%